PTU-291 Managing gi consequences of cancer treatment- what does it cost?. (22nd June 2015) - Muls, A; Marshall, C; Lalji, A; Butler, L; Andreyev, H
Abstract : Introduction: The considerable GI toxicity experienced by patients during and after cancer therapy is an increasing problem as more patients survive cancer, yet struggle to obtain adequate assessment or treatment. Method: A financial model was derived from a prospective evaluation of patients referred to a GI consequences of cancer treatment clinic, where patients are investigated and treated using an algorithm proven to be effective. The costs of assessment, investigations and prescriptions was calculated using the National Tariffs 2013/14. The clinical team includes a Consultant Gastroenterologist, a Nurse Consultant and a specialist dietetic service. This model does not include overhead costs such as administrative support, clinic space and laboratory staff costs. Results: The figures are based on the profiles of 326 consecutive patients discharged from our GI and Nutrition Team service between 01 April 2013 and 31 March 2014. This was a mixed cohort of men and women previously treated for urological (43%), gynaecological (21%), colorectal (12%), upper GI (10%) and other (14%) cancers. Initial out-patient consultation costs £192, investigations with related prescription costs (e.g. bowel preparation, SeHCAT capsule) £890 and follow up and treatment costs £438 (mean £1520 per patient). Annual NHS costs for cancer services are £5 billion, but the cost to society as a whole – including loss of productivity – is £18.3 billion (DoH, 2013). The NHS tariff for a person diagnosed with prostate cancer and treated with radiotherapy lies between £6, 000 and £9, 000. The tariff paid per woman treated with chemoradiation for cervical cancer is £14, 800. Treatment for colon cancer with a right hemicolectomy followed by adjuvant capecitebine costs £8, 300; anterior resection costs £10, 800; long course chemoradiation (capecitabine and oxaliplatin) followed by surgery and adjuvant chemotherapy (capecitebine) costs >£45, 000. Surgery for upper GI cancer costs £10, 500 while additional chemotherapy adds £2, 000-£6, 000. A pylorus preserving Whipple procedure followed by adjuvant chemoradiation with epirubicin, cisplatin and capecitebine for pancreatic cancer costs £15, 900. These are acute costs and do not include the costs of follow up or investigating and treating relapse. Conclusion: Specialist assessment and treatment of GI consequences of cancer therapies seems extremely good value in comparison to the cost of treating the cancer. So it is unclear why it has proven so difficult to obtain funding for specialist services to manage these issues which can have a devastating effect on daily activity. Lack of adequate assessment and treatment not only leads to a burden to the patient and their family, but potentially unnecessary ongoing costs to society and other clinical services. Disclosure of interest: None Declared.